Deep Brain Stimulation May Improve Quality of Life in People With Parkinson's Disease Without Affecting Caregiver Burden. Issue 2 (5th August 2013) - Oyama, Genko; Okun, Michael S.; Schmidt, Peter; Tröster, Alexander I.; Nutt, John; Go, Criscely L.; Foote, Kelly D.; Malaty, Irene A.; ,
<x xml:space="preserve">Abstract</x> Objective This study aims to investigate the influence of deep brain stimulation (DBS) on caregiver burden and quality of life in Parkinson's disease. Methods A cross‐sectional retrospective study utilizing the National Parkinson Foundation Quality Improvement Initiative clinical study was conducted. A group of 275 patients who had undergone DBS for Parkinson's disease were extracted from 2916 subjects who were included in this data base. The data were compared to an age, sex, and disease severity matched control group. A secondary analysis was then performed on two more control groups that were matched to account for presence or absence of motor fluctuations. The multidimensional caregiver strain index and Parkinson's disease quality‐of‐life questionnaire 39 summary index were compared. Results The multidimensional caregiver strain index did not differ between the DBS group (16.9 ± 11.8) and a matched non‐DBS group (16.1 ± 17.6, p = 0.618). The quality‐of‐life index was, however, significantly better in the DBS group (28.9 ± 15.6) than in the non‐DBS group (32.3 ± 17.6, p = 0.034). A secondary analysis revealed that the total caregiver strain score was lower in the no motor fluctuation control group than the other two groups (p < 0.05). Regression analysis revealed significant relationships between the quality‐of‐life index and caregiver strain index total scores (p < 0.001), between caregiver strain index total score and age at surgery (p = 0.027), and also between the interval since surgery (p = 0.048). Conclusions Although there were several limitations to this study, DBS seems to improve quality of life without significantly increasing caregiver burden.